Continuity and discontinuity in learning careers : potentials for a learning space in a changing world - Merrill, Barbara (Research on the education and learning of adults, 2018)
Continuity and Discontinuity in Learning Careers: Potentials for a Learning Space in a Changing World focuses on the new challenges and threats posed to adult education as a potential way out of the economic crisis and social change. It explores the role of adult education in relation to the continuity and discontinuity of the learning careers and identities of adults in a range of adult education learning contexts in Europe and beyond. The focus is on non-traditional students and issues of inequality such as class, gender, ethnicity, age, disability and how inequalities may enable or constrain their learning careers and identities.